Antimicrobial activities of natural plant compounds against endodontic pathogens and biocompatibility with human gingival fibroblasts. (August 2020) - Marcoux, Eve; Lagha, Amel Ben; Gauthier, Philippe; Grenier, Daniel
Highlights: Endodontic pathogens are susceptible to cinnamon oil and licorice polyphenols. Cinnamon oil is highly active against biofilm-embedded Enterococcus faecalis . Synergistic interactions between the test compounds and chlorhexidine are observed. Licorice polyphenols have no any cytotoxic effect on human gingival fibroblasts. Cinnamon oil and licorice polyphenols show promise as root canal disinfection agents. Abstract: Objectives: The aim of the present study was to investigate three licorice-derived polyphenols (glabridin, licochalcone A, licoricidin) as well as cinnamon oil for their antimicrobial activities against major endodontic pathogens: Enterococcus faecalis, Streptococcus mutans, Actinomyces israelii, Fusobacterium nucleatum, Prevotella intermedia, Porphyromonas endodontalis, and Candida albicans . The synergistic interactions between the four compounds and chlorhexidine were assessed on E. faecalis . Lastly, the biocompatibility of the tested compounds was assessed using human gingival fibroblasts. Design: Minimal inhibitory concentrations (MIC) and minimal microbicidal concentrations (MMC) were determined using a microplate dilution assay. A luminescence assay monitoring adenosine triphosphate was used to assess the antimicrobial activity of the tested compounds against E. faecalis biofilm. The synergistic effects of the tested compounds in association with chlorhexidine were evaluated using the checkerboard technique. Cytotoxicity toward human gingival fibroblasts was assessed by determination of cell metabolic activity using a colorimetric assay. Results: Cinnamon oil showed the strongest microbicidal activity. Licochalcone A, licoricidin, and glabridin had MIC values ranging from 1.56 to 25 μg/mL against the six endodontic bacterial pathogens. The natural plant compounds were active to various extents against E. faecalis embedded in a biofilm. Synergistic antibacterial effects between chlorhexidine and the compounds, mainly glabridin, were observed against E. faecalis . Following a 2-h exposure, licochalcone A, licoricidin, and glabridin demonstrated no cytotoxicity toward gingival fibroblasts at concentrations up to 50 μg/mL, while cinnamon oil and, to a lesser extent, chlorhexidine displayed some cytotoxicity. Conclusions: The present study provides evidence that the natural plant compounds tested show promise as root canal disinfection agents.